2020
DOI: 10.3354/meps13219
|View full text |Cite
|
Sign up to set email alerts
|

A decade of monitoring Atlantic cod Gadus morhua spawning aggregations in Massachusetts Bay using passive acoustics

Abstract: Atlantic cod Gadus morhua populations in the northeast USA have failed to recover since major declines in the 1970s and 1990s. To rebuild these stocks, managers need reliable information on spawning dynamics in order to design and implement control measures; discovering cost-effective and non-invasive monitoring techniques is also favorable. Atlantic cod form dense, site-fidelic spawning aggregations during which they vocalize, permitting acoustic detection of their presence at such times. The objective of thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 67 publications
(80 reference statements)
0
18
1
Order By: Relevance
“…This homogeneity is essential to formalize their use in PAM and to be able to distinguish the target species. Several studies in marine environments have shown long-term consistency (10-17 years) in the acoustic features of fish from the same geographic areas, including the brown meagre Sciaena umbra Linnaeus, 1758 (Parmentier et al, 2018) and Atlantic cod Gadus morhua Linnaeus, 1758 (Caiger et al, 2020), further supporting the usefulness of PAM for fishes.…”
Section: Discussionmentioning
confidence: 76%
“…This homogeneity is essential to formalize their use in PAM and to be able to distinguish the target species. Several studies in marine environments have shown long-term consistency (10-17 years) in the acoustic features of fish from the same geographic areas, including the brown meagre Sciaena umbra Linnaeus, 1758 (Parmentier et al, 2018) and Atlantic cod Gadus morhua Linnaeus, 1758 (Caiger et al, 2020), further supporting the usefulness of PAM for fishes.…”
Section: Discussionmentioning
confidence: 76%
“…The Cozumel Paraiso Reef study focused on the splendid toadfish, demonstrated the value of PAM survey data as a tool for understanding vulnerable species and habitats that may lead to conservation initiatives. We present the first description of acoustic recordings of S. splendidus vocalizations that can be effectively used by scientists and managers to determine the species' occurrence, habitat range, and behavior and ecology, including mating and spawning (sensu Bertucci, Lejeune, Payrot, & Parmentier, 2015; Caiger et al, 2020; Luczkovich, Pullinger, Johnson, & Sprague, 2008; Wall et al, 2014). Recent quantitative approaches allow for estimating population density and abundance based on calling patterns (Marques et al, 2013), and these approaches could also be applied to S. splendidus .…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the sound level of fish choruses provides insights into fish population abundances (Rowell et al, 2012;Rowell et al, 2017). PAM has already been proved as a valuable tool for locating FSAs of exploited species, such as cod, haddock and other gadidae (Rountree et al, 2006;Hawkins & Picciulin, 2019;Caiger et al, 2020). In the future, the use of fixed, autonomous recorders and of mobile acoustic sensors (e.g.…”
Section: Introductionmentioning
confidence: 99%